Молюски роду Planorbis (Gastropoda, Planorbinae) фауни України: діагностика, особливості поширення та екології - Уваєва, О.І. (Вестник зоологии, 2007)
Анализ конхиологических и анатомических характеристик видов рода Planorbis с применением методов многомерной статистики позволяет четко дифференцировать 3 вида: P. planorbis, P. philippianus, P. carinatus. Установлено, что диагностическое значение имеют соотношение ширины последнего и предпоследнего оборотов раковины, ширины предпоследнего и третьего оборотов раковины, а также соотношение длины препуциума и длины мешка пениса. Расширены сведения о хорологических и экологических особенностях моллюсков рода Planorbis. The complex analysis of conchological and anatomical characteristics of species of the genus Planorbis using methods of multi-measuring statistics allows precise identification of 3 species — P. planorbis, P. philippianus, P. carinatus. The ratio of width of last whorl (measured from apical side) to width of penultimate whorl, ratio of width of penultimate whorl to width of prepenultimate whorl, ratio of praeputium length to penis sheath length are shown to have diagnostic importance. New data on distribution and ecology of mollusks of the genus Planorbis are provided.